Comparison of Biological and Conventional Synthetic DMARDS Treatment Response for Psoriatic Arthritis with Associated Fibromyalgia - Bushra,; Rasheed, Khurram; Khan , Muhammad Shahid; Bukhari, Syeda Kinza; Sheen, Irfan Najam; Batool, Sidra (Indus Journal of Bioscience Research, 2025)
Objective: To compare the good treatment responses of biologic and conventional synthetic DMARDs in psoriatic arthritis (PsA) patients with associated fibromyalgia. Study Design: Randomized controlled trial. Duration and Place of Study: Conducted from January 2024 to December 2024 at the Department of Medicine, CMH Multan. Methodology: A total of 110 patients (age 18-70) with confirmed PsA and fibromyalgia for at least 6 months were randomly assigned into two groups (n=55 each). Group A received biologic DMARDs, including adalimumab, etanercept, infliximab, or secukinumab. Group B received conventional synthetic DMARDs, including methotrexate, leflunomide, or sulfasalazine. The primary endpoint was the therapeutic response at 6 months, measured by Clinical Disease Activity Index (CDAI), Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), and Health Assessment Questionnaire Disability Index (HAQ-DI). Results: Both groups showed significant demographic and clinical variation, but no significant difference was found in the overall therapeutic response between the two groups (p = 0.127). Functional disability, as measured by HAQ-DI, emerged as a key predictor of therapeutic response, with patients exhibiting higher functional impairment showing more favorable treatment outcomes. Conclusion: Biologic and conventional synthetic DMARDs exhibited comparable therapeutic efficacy in PsA patients with fibromyalgia.